1975
DOI: 10.1093/oxfordjournals.aje.a112071
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Hepatitis B in Hospital Personnel

Abstract: To identify occupational categories and work areas of possible risk for acquisition of nosocomial hepatitis B by hospital personnel, serologic sampling for hepatitis B surface antigen (HBSAg) and antibody (anti-HBS) by radioimmunoassay was carried out in 513 employees of a large metropolitan hospital serving predominantly indigent patients. HBSAg was detected in 0.7%, HBSAg and anti-HBS in 0.4%, and anti-HBS in 13.3% of the study population. No significant difference in seropositivity was noted between sexes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
1
3

Year Published

1978
1978
1993
1993

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(27 citation statements)
references
References 0 publications
4
18
1
3
Order By: Relevance
“…The greatest benefits are obtained when the vaccine is administered in a non-detectable high-risk period, when the prevalence of immunity seems lower due to an elevated attack ratio (15). Our data on risk factors are in agreement with other authors; professional exposure to blood (13,17), length of patient contact (16), and length of time working in the same position (6). Nurses have the highest risk of infection (2, 6, 10,14).…”
Section: Possibility Of Being Immunesupporting
confidence: 90%
“…The greatest benefits are obtained when the vaccine is administered in a non-detectable high-risk period, when the prevalence of immunity seems lower due to an elevated attack ratio (15). Our data on risk factors are in agreement with other authors; professional exposure to blood (13,17), length of patient contact (16), and length of time working in the same position (6). Nurses have the highest risk of infection (2, 6, 10,14).…”
Section: Possibility Of Being Immunesupporting
confidence: 90%
“…Wild honey (found in the forest and for sale at the village market) 1 litre Strong tea brewed from eucalyptus leaves (available everywhere) 2 The cost price comes to 021p/5 ml. We think it is reasonable to sell it for 3 75p, which is less than what people used to pay for cough mixture from the pharmacy.…”
Section: Discussionmentioning
confidence: 99%
“…2 Reports of transmission in the other direction-that is, from staff to patients-are uncommon, and attempts to assess their frequency were considered unnecessary in Britain, where both the incidence of acute hepatitis B and the prevalence of hepatitis B surface antigen (HBsAg) carriage are low. After an outbreak of acute hepatitis B among patients, however, which was caused by a gynaecologist who was a symptomless carrier of the infection,3 a study was designed to estimate the frequency of such events.…”
Section: Introductionmentioning
confidence: 99%
“…Hepatitis B has long been recognized as an occupational hazard to health care personnel (1,10,11,13,15,16). Within the hospital setting itself certain occupational categories and work areas were identified as associated with a high risk of hepatitis B infection.…”
Section: Introductionmentioning
confidence: 99%
“…are said to be at an increased risk of acquiring the infection (2,12,15). Several studies using serological markers of hepatitis B virus have shown a significant positive association between blood exposure and seropositivity of hospital employees (11).…”
Section: Introductionmentioning
confidence: 99%